2011
DOI: 10.1016/j.bbadis.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Adult human CD133/1+ kidney cells isolated from papilla integrate into developing kidney tubules

Abstract: Approximately 60,000 patients in the US are waiting for a kidney transplant due to genetic, immunologic and environmentally caused kidney failure. Adult human renal stem cells could offer opportunities for autologous transplant and repair of damaged organs. Current data suggest that there are multiple progenitor types in the kidney with distinct localizations. In the present study, we characterize cells derived from human kidney papilla and show their capacity for tubulogenesis. In situ, nestin+ and CD133/1+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 86 publications
6
48
0
3
Order By: Relevance
“…The neonatal human heart is a rich source of CPC bearing markers such as SSEA4, Isl1, Nkx2.5, and c-Kit. In addition to our report of myocardial SSEA4 localization (Amir et al, 2008), SSEA4 expression has been previously only reported in adult human kidney (Ward et al, 2011). Isl1 + CPC have also been localized to the atrium (Laugwitz et al, 2005).…”
Section: Markers Of Cpc In the Postnatal Heartsupporting
confidence: 71%
“…The neonatal human heart is a rich source of CPC bearing markers such as SSEA4, Isl1, Nkx2.5, and c-Kit. In addition to our report of myocardial SSEA4 localization (Amir et al, 2008), SSEA4 expression has been previously only reported in adult human kidney (Ward et al, 2011). Isl1 + CPC have also been localized to the atrium (Laugwitz et al, 2005).…”
Section: Markers Of Cpc In the Postnatal Heartsupporting
confidence: 71%
“…The human renal papilla has also been reported to contain epithelial Oct4-expressing prominin/CD133 + cells in loops of Henle that form epithelial structures in vitro. 48,49 Our kidney MSClike cells are derived from collecting duct and home specifically back to that tubular segment, suggesting no overlap with these studies.…”
Section: Discussionmentioning
confidence: 81%
“…35-010-CV, Corning) and 1% penicillin/streptomycin. Bioreactors were transferred to an incubator and perfused at 5 mL/min for at least 1 h. For seeding, perfusion was halted, and 40 million immortalized Madin-Darby canine kidney (MDCK) cells 21,22 or 6.25 million primary human renal papillae-derived CD133/1 + cells from anonymous cadaveric donors 23 were loaded into a syringe (2 mL volume) and manually injected at *2 mL/min…”
Section: Recellularizationmentioning
confidence: 99%
“…Placing this finding in context of other methods of cell delivery into the scaffold, this method of tubular repopulation is more efficient compared to infusion of cells through the ureter or artery at flow rates (e.g., <1 mL/min) which others have shown to preferentially restrict cells to glomeruli and nearby arterioles. 7,10,15,16 We additionally infused primary CD133/1 + human renal progenitor cells recovered from the renal papillae 23 using the arterial seeding method to validate the bioreactor system using primary cells. We observed similar dispersion of the cells throughout the renal cortex over a 3-and 7-day culture period (Fig.…”
mentioning
confidence: 99%